To solve for a, we need to simplify the equation:
3(x + 2) - 6 = 3x
Distribute 3 to both terms inside the parentheses:
3x + 6 - 6 = 3x
Combine like terms:
3x = 3x
Now, we see that the variable x is eliminated on both sides of the equation. This means that the equation is true for any value of x. Therefore, the equation has infinite solutions.
The correct answer is: The equation has infinite solutions.
Solve for a to determine if the equation has one, none, or infinite solutions.
3(x + 2) - 6 = 3x (1 point)
The equation has one solution: x = 3
The equation has one solution: x = -3
The equation has no solution.
The equation has infinite solutions.
1 answer